2019
DOI: 10.3390/md17070391
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharide Ameliorates Nonalcoholic Fatty Liver Disease (NAFLD) in Diet-Induced Obese Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a global epidemic, and there is no standard and efficient therapy for it. Chitosan oligosaccharide (COS) is widely known to have various biological effects, and in this study we aimed to evaluate the liver-protective effect in diet-induced obese mice for an enzymatically digested product of COS called COS23 which is mainly composed of dimers and trimers. An integrated analysis of the lipidome and gut microbiome were performed to assess the effects of COS23 on lipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
(64 reference statements)
2
33
0
Order By: Relevance
“…Moreover, a fructo-oligosaccharides supply reversed high-fat diet feeding-induced reduction in level of Bifidobacteria and increase in plasma endotoxin content in mice [108]. Evidence from integrated lipidome and gut microbiome uncovered that chitosan oligosaccharide serves to ameliorate hepatic injury, steatosis, and inflammation as well as to reinforce the intestinal barrier [109]. Also, this oligosaccharide induced a reduction in the cecal abundance of Mucispirillum and an elevation in the content of Coprococcus [109].…”
Section: Functional Oligosaccharidesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, a fructo-oligosaccharides supply reversed high-fat diet feeding-induced reduction in level of Bifidobacteria and increase in plasma endotoxin content in mice [108]. Evidence from integrated lipidome and gut microbiome uncovered that chitosan oligosaccharide serves to ameliorate hepatic injury, steatosis, and inflammation as well as to reinforce the intestinal barrier [109]. Also, this oligosaccharide induced a reduction in the cecal abundance of Mucispirillum and an elevation in the content of Coprococcus [109].…”
Section: Functional Oligosaccharidesmentioning
confidence: 96%
“…Evidence from integrated lipidome and gut microbiome uncovered that chitosan oligosaccharide serves to ameliorate hepatic injury, steatosis, and inflammation as well as to reinforce the intestinal barrier [109]. Also, this oligosaccharide induced a reduction in the cecal abundance of Mucispirillum and an elevation in the content of Coprococcus [109]. Besides, the contribution of oligosaccharides to bile acid secretion and bile acid pool kinetics has been demonstrated in various animal models [110][111][112].…”
Section: Functional Oligosaccharidesmentioning
confidence: 96%
“…The incidence of NAFLD in western countries has reached 30%, which has seriously affected worldwide healthcare (Abdelmalek, 2016;Younossi et al, 2016;Fiorucci et al, 2018). NAFLD is characterized by excessive fat deposition in hepatocytes caused by other definite liver-damaging factors besides alcohol and can progress to non-alcoholic steatohepatitis, liver cirrhosis and hepatocellular carcinoma (Qian et al, 2019). Thus, the treatment of NAFLD is a focus of world health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In pre-clinical studies, an improvement in blood lipids has been reported after probiotic and prebiotic treatments [51,61,67,68,73,74]. Reduction in TC due to single and combined probiotic treatment (Lactobacillus) has been linked to the activation of the transcription of genes belonging to the liver X receptors (LXR) axis, inducing TC reverse transport and augmenting the conversion of TC to bile acids [75].…”
Section: Effect Of Probiotics Prebiotics and Synbiotics On Blood Lipidsmentioning
confidence: 99%